Innenansicht des Museum of Popular Art im Palast des Ataoja in Osogbo (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Museums; Art; Exhibitions; Interior decoration; Leopard; Hausa (African people); Art Exhibition; Ataoja; Osogbo; Nigeria; Cultural Centre